Body and emotion : the aesthetics of illness and healing in the Nepal Himalayas - Desjarlais, Robert R. (Series in contemporary ethnography., 1992)
Body and Emotion is a study of the relationship between culture and emotional distress, an examination of the cultural forces that influence, make sense of, and heal severe pain and malaise. In order to investigate this relationship, Robert R. Desjarlais served as an apprentice healer among the Yolmo Sherpa, a Tibetan Buddhist people who reside in the Helambu region of northcentral Nepal. In his quest to understand illness among Yolmo villagers, especially a prevalent malady known as "soul loss," Desjarlais goes beyond an exploration of causes and cures to analyze the "aesthetics" of everyday living and their relation to bodily experience, emotional distress, and ritual healing. In contrast to other recent accounts of "symbolic healing," which posit that shamanic rites heal by manipulating the symbolic categories that define a patient, the author contends that a shaman's rites work chiefly to change how a patient feels. A concern for the sensory influences the style of the book, as Desjarlais bids for an ethnography of the tactile, the visceral, the unspoken. Body and Emotion calls for a more sentient anthropology, moves beyond meaning-centered approaches to pain and the body, and outlines the profound role of aesthetic sensibilities in everyday life. Body and Emotion is an extraordinary work that will be of particular value to students and scholars in the fields of anthropology, psychology, Asian studies, and religious studies.